Systematic review of the barriers to social enterprise performance using an institutional framework - Yusuf Iskandar; Joeliaty Joeliaty; Umi Kaltum; Hilmiana Hilmiana (Cogent Business & Management, 2022)
This study uses a systematic review in examining the factors that may have a negative impact on social enterprises in Indonesia within an institutional framework. An institutional framework was used in this study to update existing studies. Moreover, this study is also intended to explore the obstacles that may exist in improving the performance of social entrepreneurs in Indonesia. A systematic review of the literature is the approach used in this analysis. A researcher can draw plausible observations and present generalizable research by carrying out a comprehensive literature analysis, which is found by predefined literature search techniques. This study was carried out in two stages to complement the systematic analysis, as described below. Eighteen references were found using the literature review criteria and used in the qualitative synthesis. The idea of social entrepreneurship was introduced by the Indonesian government in 2015. Social entrepreneurship has been impacted by the global downturn, political instability, government bureaucracy, and society. Building a solid regulatory system for social enterprise would aid in the success of these businesses. The Indonesian government should provide an awareness center as well as give recommendations to assist the community in navigating the complex cultural landscape. The significance of this study is that it has the potential to affect policy decisions in order to change the structural climate for social entrepreneurship. International investors who want to start a social enterprise in Indonesia can also learn about the institutional structure and how it affects their venture.
Keywords: 650; Indonesia; social enterprise; barriers to improve; institutional framework